Showing that echelon matrix and its transpose have the same determinant

linear algebramatrices

The book I'm working through (Calculus and Analysis in Euclidean Spaces by Shurman et al.) is introducing determinant in a characterizing and descriptive way, rather than just handing out it's algorithm. Therefore as I have to show that for a square echelon matrix $E$ it holds that $\det{E} = \det{E^T}$, I'm guessing that the proof "excepts" the usage of the determinant as a function of the rows of the input matrix. So without further ado: If $E = I$, then $\det{E} = \det{I} = 1$, as the determinant is normalized. But what about if $E \neq I$? Then necessarily at least the last row of $E$ is full of zeroes, and thus $\det{(E)} = \det{(r_1,\dots,r_{n-1},0)} = 0\cdots c \det{(e_1,\dots,e_n)} = 0 \cdot c \cdot 1 = 0, c \in \mathbb{R}$.

But how do you argue about the transpose? So far the "only" tools that have been given are the elementary matrices of $S_{i, a}, T_{i;j}, R_{i;j,a}$ which scales the ith row by $a$, swap the $i$th and $j$th row and add to the $i$th row the $j$th row scaled by $a \in \mathbb{R}$. It can be assumed that the determinants of these matrices are equal to their transposes, and $\det{S_{i, a}} = a, \det{T_{i;j}} = -1, \det{R_{i;j,a}} = 1$.

Best Answer

Based on what you've said, you know that the determinant is alternating, multilinear, and $\det(I) = 1$ (It can be shown that these three properties uniquely characterize the determinant). Thus we can expand out the determinant using the multilinearity in the straightforward way: \begin{align} \det(A) &= \det(a_1, \dots, a_n) \\ &= \sum_{i_1 = 1}^{n}a_{i_1, 1}\det(e_{i_1}, a_2, \dots, a_n) \\ &= \sum_{i_1 = 1}^{n}\sum_{i_2 = 1}^{n}a_{i_1, 1}a_{i_2, 2}\det(e_{i_1}, e_{i_2}, a_3, \dots, a_n) \\ &= \dots \\ &= \sum_{i_1, \dots, i_n = 1}^{n}a_{i_1, 1}\dots a_{i_n, n}\det(e_{i_1}, \dots, e_{i_n}). \end{align} By the alternating property, if two columns of a matrix are equal, then it's determinant is $0$. Thus we only need to sum over the permutations of $\{1, \dots, n\}$: \begin{align} \det(A) &= \sum_{i_1, \dots, i_n = 1}^{n}a_{i_1, 1}\dots a_{i_n, n}\det(e_{i_1}, \dots, e_{i_n}) \\ &= \sum_{\sigma \in S_n}a_{\sigma(1), 1}\dots a_{\sigma(n), n}\det(e_{\sigma(1)}, \dots, e_{\sigma(n)}). \end{align} By the alternating property and the property $\det(I) = 1$, we have $\det(e_{\sigma(1)}, \dots, e_{\sigma(n)}) = (-1)^{\sigma}\det(e_1, \dots, e_n) = (-1)^\sigma$ for any $\sigma \in S_n$, where $(-1)^{\sigma}$ denotes the sign of $\sigma$ (note $(-1)^{\sigma} = (-1)^{\sigma^{-1}}$). Thus \begin{align} \det(A) &= \sum_{\sigma \in S_n}a_{\sigma(1), 1}\dots a_{\sigma(n), n}(-1)^{\sigma}. \\ \end{align} With this general formula in hand, proving $\det(A) = \det(A^T)$ is easy. We have \begin{align} \det(A) &= \sum_{\sigma \in S_n}a_{\sigma(1), 1}\dots a_{\sigma(n), n}(-1)^{\sigma} \\ &= \sum_{\sigma \in S_n}a_{1, \sigma^{-1}(1)}\dots a_{n, \sigma^{-1}(n)}(-1)^{\sigma} \\ &= \sum_{\sigma \in S_n}a_{1, \sigma^{-1}(1)}\dots a_{n, \sigma^{-1}(n)}(-1)^{\sigma^{-1}} \\ &= \sum_{\tau \in S_n}a_{1, \tau(1)}\dots a_{n, \tau(n)}(-1)^{\tau} \\ &= \det(A^T). \end{align}